MUATAN TITIK NOL BERBAGAI BAHAN ORGANIK, PENGARUHNYA TERHADAP KAPASITAS TUKAR KATION DI LAHAN TERDEGRADASI - Sri Hartati; Slamet Minardi; Dwi Priyo Ariyanto (Faculty of Agriculture, Universitas Sebelas Maret, 2013)
Title : Zero Point of Charge of Various Organic Fertilizer : The Effect on Soil Cation Exchange Capacity in Degraded Lands. Zero Point of Charge (ZPC) is an important variable in describing the mechanism of reversible surface charge primarily on weathered soil dominated by variable charge. ZPC is a certain pH when the surface charge is electrically neutral or zero (pHo). The presence of organic matter effect on the nature of the charge in the soil. Research goals include: 1). Obtaining information kinds of organic fertilizer with low of pHo, 2) Knowing the behavior of pHo and net charge of soil, 3) Knowing the influence of pHo on the soil cation exchange capacity. This study is an experimental functional relationship variables approach through experiments. The experiments were conducted at Greenhouse of Agriculture Faculty, Sebelas Maret Univercity. The basic design used was completely randomized design of a single factor. The treatment is done as follows: P0 = soil without the addition of organic fertilizers, P1 = soil with the addition of cow manure 5 tons / ha, P2 = soil with the addition of chicken manure 5 tons / ha, P3 = soil with the addition of quail manure s 5 tons/ ha, P4 = soil with the addition of goat manure 5 tons / ha, P5 = soil with the addition of bokashi 5 tons / ha, P6 = soil with the addition of rice straw compost 5 tons / ha, P7 = soil by adding compost hyacinth 5 ton / ha. P8 = soil by adding compost of Titonia 5 tons / ha and each treatment was repeated 3 times. Analysis of the quality of organic fertilizers include: levels of lignin and polyphenols, C/N, pH , pHo, humic acid and fulvic acid. The soil analysis includes the C-organic soil, total N, C / N, pH , pHo, CEC. The results showed that the zero point of charge (pHo) is the lowest organic fertilizer chicken manure (4.52). Obtained a close relationship between the difference in pH H2O with pHo with cation exchange capacity. Highest cation exchange capacity achieved in the treatment of chicken manure.